DEHYDRATION OF NATURAL STILBITE: AN IN SITU FTIR STUDY - Prasad P.S.R.; Prasad K.S.; Murthy S.R. (My University, 2005)
The dehydration behavior of a natural stilbite sample from Poona (India) was investigated by in situ FTIR. The thermal induced variations of the water molecule bending (ν2) mode around 1653 cm−1, the stretching (ν3 and ν1) modes around 3587 and 3426 cm−1, and the corresponding second-order modes in the wavenumber region 4000–8000 cm−1 were followed as indicative of the dehydration process. The observed spectral variations indicate that stilbite undergoes a transformation at about 448 K due to the loss of half of the original content of water molecules. The rehydration of stilbite is partial in samples heated up to 630 K. Concerning both the dehydration and rehydration behaviors of stilbite, our results are in concert with those proposed in the literature. In addition, the growth of a new mode around 4550 cm−1 is observed in the temperature range 430–650 K and may indicate the presence of hydroxyl groups created by the breaking of the T-O-T linkages.